Efeitos do foam roller sobre a dor lombar e o desempenho de corredores - Porto, Liege Brum (2018)
Low back pain of non-specific cause in runners can be influenced by mechanical overloads associated with joint and muscle stiffness in the lower extremities and low back spine. It leads to reduce range of motion, pelvis-knee coordination, and lower speed during running. These factors may increase the intensity of low back pain, resulting in postural dysfunctions that limit performance of running and the sports practice. Miofascial self release using foam roller, in theory, could change the muscle stiffness and contribute to improve range of motion, which may contribute positively to the running technique. Runners have been using foam roller, but still there are a few available evidences concerning its effectiveness. In this study we determine the effects of foam roller application on running performance in participants with and without low back pain of lower intensity. In 20 runners (10 with low back pain and 10 without low back pain) we evaluated self reported pain, low back spine mobility, and range of motion in protocols of 5km running. Running protocols were conducted after foam roller or control (stretching) interventions, and low back spine mobility was evaluated before and after the interventions. Foam roller did not affect low back mobility. Foam roller increased pelvis range of motion in low back pain group, and knee and ankle range of motion of participants without low back pain. Such effects were found at different moments of the running protocols. After control intervention, low back pain group increased ankle range of motion, and the group without pain increased hip range of motion. In summary, the acute effects of foam roller were not consistent in runners.